Enhancing students' interpersonal communication through a Kato Nan Ampek-based group counseling cognitive-behavioral model - Nining Maizura; Henny Indreswari; Nur Eva; Khairul Bariyyah (ENLIGHTEN (Jurnal Bimbingan dan Konseling Islam), 2025)
In recent years, high school students have faced increasing challenges in establishing effective interpersonal communication, a critical skill for academic success and personal development. This study developed a cognitive-behavioral group counseling guide that integrates Kato Nan Ampek values to enhance students' interpersonal communication skills. The research followed a Research and Development (R&D) approach, including preliminary studies, product design, expert validation, and limited trials. Validation by experts in counseling, cultural studies, and educational media, as well as input from potential users, affirmed the guide’s theoretical feasibility. The guide was further evaluated through its application in a school setting, where it demonstrated substantial effectiveness in improving students' interpersonal communication. The results highlight the guide’s practical value for school counselors, emphasizing the significance of integrating local cultural values into counseling practices. This study underscores the potential of culturally grounded interventions in enhancing communication skills and offers insights for future research that could explore its broader applicability across diverse educational contexts.